Intraluminal Duplication of the Terminal Ileum with Ectopic Gastric Mucosa in an Infant: A Rare Cause of Intussusception - Filomena Valentina Paradiso; Laura Merli; Sara Silvaroli; Vincenzo Fiorentino; Riccardo Ricci; Lorenzo Nanni (Hindawi Limited, 2020)
Enteric duplication cysts are rare malformations mostly diagnosed before the age of two, with varied clinical presentations. Ectopic gastrointestinal epithelium can be present, and management involves surgical resection. A three-month-old girl presented with rectal bleeding due to an ileocolic intussusception. Abdominal ultrasound revealed a target sign in the right upper part of the abdomen. At hydrostatic contrast enema, an incomplete reduction of the intussusception was obtained: only a trickle of contrast material entered the terminal ileum. An exploratory laparotomy ensued with manual reduction of the intussusception. At the end of the maneuver, a soft intraluminal mass was palpated within the ileocecal valve. Thus, an ileocecal resection was performed. At histology, an intraluminal enteric duplication cyst was documented, containing ectopic gastric mucosa. Secondary intussusception should be suspected even in infants in case of abnormal findings at hydrostatic contrast enema. Intraluminal enteric duplication cysts may be a rare cause of intussusception.